Uji Hemaglutinasi Assay pada Hemolimf Spodoptera exigua yang diberi Perlakuan Botani Pestisida - Suryani, A.Irma; Anggraeni, Tjandra (Fakultas MIPA UNM, 2019)
Abstract. The larval stage of the armyworm (Spodoptera exigua), has a high and polyphagous feeding activity so that these insects have the potential to be pests in agriculture. The use of botanical pesticides in this case Mirabilis jalapa, is expected to control agricultural pests so that research on the immune system of S. exigua larvae is carried out by observing lectins that play a role in analyzing foreign molecules that enter the insect's body. The results were obtained, the higher the M. jalapa concentration, at the concentration of M. jalapa 0.4% and 0.8%, the lower the hemolymf agglutination titers. This is thought to decrease the binding capacity of lectins to foreign molecules. So that M. jalapa has the potential to be used as an environmentally friendly botanical pesticide.Keywords: agricultural pests, botanical pesticides, lectin agglutination.